The silence of Language - Gérard Dessons (Gragoatá, 2005)
We propose here to consider the silence as a fully category of language, contrary to the preconceived idea that it is a negative reality (an absence of words). Unlike other approaches that do not reject the silence outside language (the classical moralism, rhetoric, pragmatic linguistics), we present a poetic approach to the problem, defining the silence as something we do not know how to listen in language, but that literature allows it to manifest.